Shareholder wealth effects of seasoned share issues in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University - Anderson, Hamish David (Massey University, 2003)
This thesis investigates shareholder wealth impact surrounding the issue of seasoned equity by companies listed on the New Zealand Stock Exchange. The first two essays contained in this thesis examine the wealth impact of stock dividends. Technically, issuing new shares through the mechanism of stock dividends is simply a cosmetic accounting change and therefore should not have any impact on shareholder wealth. However, consistent with other international markets we find shareholder wealth is impacted around the announcement date and again on the ex-dates of stock dividends. In both stock dividend essays, we find evidence that investors value imputation tax credits attached to stock dividends. One of the major theories explaining stock dividend ex-dates in the US is the odd-lot cost theory but no direct test has been possible in that market. The New Zealand market enables us to directly test the odd-lot cost argument by examining the ex-date effect when odd-lot costs are present to a later period when they were eliminated. We find evidence supporting the odd-lot cost theory. The final essay contained in this thesis examines the announcements of new shares issued through the private placement mechanism. In New Zealand, private placement price contains important information regarding firm quality. In examining volumes surrounding private placement we find evidence supporting market commentators' conjecture that some placement purchasers may be exploiting relatively weak regulations by immediately reselling the new shares on the market for an instant profit.
Keywords: Stock dividends; New Zealand; Shareholder wealth; Fields of Research::350000 Commerce, Management, Tourism and Services::350300 Banking, Finance and Investment